Laporan baru tungau Tarsonemus bilobatus Suski dan karakter utama tungau lain pada daun tanaman jeruk di Pulau Jawa, Indonesia - Hendri Hermawan; Sugeng Santoso; Aunu Rauf (Jurnal Entomologi Indonesia, 2021)
Citrus is one of the most important fruit crops in Indonesia. One of the main problems in citrus production is mite infestation. Many mite species were reported attacking citrus around the world. This study was aimed to identify mites and describe the main characters of various species of mites on citrus in Java, Indonesia. Sampling was carried out at the location of citrus plantations and citrus plants in the yard of the house which was carried out purposively. In a large planting area, sampling was carried out on 10 citrus trees that showed symptoms of mite attack. The identification process is carried out by a mounting process to obtain specimens that can be observed under a compound microscope using PVA. Eight species of mites were collected from 8 various of citrus from 15 locations. Six mites species were identified as phytophagous, i.e., Panonychus citri McGregor, Eotetranychus sp., Eutetranychus sp. (Family Tetranychidae), Brevipalpus phoenicis (Geijskes) (Family Tenuipalpidae), Tarsonemus bilobatus Suski (Family Tarsonemidae), and Phyllocoptruta oleivora (Ashmead) (Family Eriophyidae). Meanwhile, the other two species, Amblyseius sp. (Family Phytoseiidae) and Cheletogenes ornatus (Canestrini & Fanzago) (Family Cheyletidae) were predators. Unidentified mites were Family Tydeidae and Winterschmidtiidae. According to Regulation No. 31 of 2018, P. citri and Ph. oleivora are quarantine pest. T. bilobatus is firstly reported in Indonesia.